The role of melanin pathways in extremotolerance and virulence of Fonsecaea revealed by de novo assembly transcriptomics using illumina paired-end sequencing - Li, X.Q. (Stud Mycol, 2016)
Melanisation has been considered to be an important virulence factor of Fonsecaea monophora. However, the biosynthetic mechanisms of melanisation remain unknown. We therefore used next generation sequencing technology to investigate the transcriptome and digital gene expression data, which are valuable resources to better understand the molecular and biological mechanisms regulating melanisation in F. monophora. We performed de novo transcriptome assembly and digital gene expression (DGE) profiling analyses of parent (CBS 122845) and albino (CBS 125194) strains using the Illumina RNA-seq system. A total of 17 352 annotated unigenes were found by BLAST search of NR, Swiss-Prot, Gene Ontology, Clusters of Orthologous Groups and Kyoto Encyclopedia of Genes and Genomes (KEGG) (E-value <1e‒5). A total of 2 283 unigenes were judged to be the differentially expressed between the two genotypes. We identified most of the genes coding for key enzymes involved in melanin biosynthesis pathways, including polyketide synthase (pks), multicopper oxidase (mco), laccase, tyrosinase and homogentisate 1,2-dioxygenase (hmgA). DEG analysis showed extensive down-regulation of key genes in the DHN pathway, while up-regulation was noted in the DOPA pathway of the albino mutant. The transcript levels of partial genes were confirmed by real time RT-PCR, while the crucial role of key enzymes was confirmed by either inhibitor or substrate tests in vitro. Meanwhile, numbers of genes involved in light sensing, cell wall synthesis, morphology and environmental stress were identified in the transcriptome of F. monophora. In addition, 3 353 SSRs (Simple Sequence Repeats) markers were identified from 21 600 consensus sequences. Blocking of the DNH pathway is the most likely reason of melanin deficiency in the albino strain, while the production of pheomelanin and pyomelanin were probably regulated by unknown transcription factors on upstream of both pathways. Most of genes involved in environmental tolerance to oxidants, irradiation and extreme temperatures were also assembled and annotated in transcriptomes of F. monophora. In addition, thousands of identified cSSR (combined SSR) markers will favour further genetic linkage studies. In conclusion, these data will contribute to understanding the regulation of melanin biosynthesis and help to improve the studies of pathogenicity of F. monophora.